Specific DNA binding of archaeal histones HMfA and HMfB - Erkelens, Amanda M.; Henneman, Bram; van der Valk, Ramon A.; Kirolos, Nancy C. S.; Dame, Remus T. (Frontiers in Microbiology, 2023)
In archaea, histones play a role in genome compaction and are involved in transcription regulation. Whereas archaeal histones bind DNA without sequence specificity, they bind preferentially to DNA containing repeats of alternating A/T and G/C motifs. These motifs are also present on the artificial sequence “Clone20,” a high-affinity model sequence for binding of the histones from Methanothermus fervidus. Here, we investigate the binding of HMfA and HMfB to Clone20 DNA. We show that specific binding at low protein concentrations (<30 nM) yields a modest level of DNA compaction, attributed to tetrameric nucleosome formation, whereas nonspecific binding strongly compacts DNA. We also demonstrate that histones impaired in hypernucleosome formation are still able to recognize the Clone20 sequence. Histone tetramers indeed exhibit a higher binding affinity for Clone20 than nonspecific DNA. Our results indicate that a high-affinity DNA sequence does not act as a nucleation site, but is bound by a tetramer which we propose is geometrically different from the hypernucleosome. Such a mode of histone binding might permit sequence-driven modulation of hypernucleosome size. These findings might be extrapolated to histone variants that do not form hypernucleosomes. Versatile binding modes of histones could provide a platform for functional interplay between genome compaction and transcription.